Drinking Like an Adult? Trajectories of Alcohol Use Patterns Before and After College Graduation. (19th February 2016) - Arria, Amelia M.; Caldeira, Kimberly M.; Allen, Hannah K.; Vincent, Kathryn B.; Bugbee, Brittany A.; O'Grady, Kevin E.
Abstract : Background: College students who engage in high‐risk drinking patterns are thought to "mature out" of these patterns as they transition to adult roles. College graduation is an important milestone demarcating this transition. We examine longitudinal changes in quantity and frequency of alcohol consumption between the college years and the 4 years after graduation and explore variation in these changes by gender and race/ethnicity. Methods: Participants were 1, 128 college graduates enrolled in a longitudinal prospective study of health‐risk behaviors. Standard measures of alcohol consumption were gathered during 8 annual personal interviews (76 to 91% annual follow‐up). Graduation dates were culled from administrative data and self‐report. Spline models, in which separate trajectories were modeled before and after the "knot" of college graduation, were fit to 8 annual observations of past‐year alcohol use frequency and quantity (typical number of drinks/drinking day). Results: Frequency increased linearly pregraduation, slightly decreased postgraduation, and then rebounded to pregraduation levels. Pregraduation frequency increased more steeply among individuals who drank more heavily at college entry. Quantity decreased linearly during college, followed by quadratic decreases after graduation. Conclusions: Results suggest that the postcollege "maturing‐out" phenomenon might be attributable to decreases in alcohol quantity but not frequency. High‐frequency drinking patterns that develop during college appear to persist several years postgraduation. Abstract : In this young‐adult sample, college graduation was a critical turning point in alcohol drinking patterns, in that the pre‐ and post‐graduation rates of change in frequency and quantity were significantly different. Drinking frequency increased throughout college and leveled off thereafter, whereas quantity (number of drinks per drinking day) decreased steadily both during and after college. Findings extend prior research on the phenomenon of maturing out of heavy drinking patterns by focusing on college graduation as a turning point.